HZ-A-018, a novel inhibitor of Bruton tyrosine kinase, exerts anti-cancer activity and sensitizes 5-FU in gastric cancer cells - Liu, Danjing; Xu, Wei; Lin, Bin; Ji, Cong; Shen, Minmin; Shen, Shuying; Ma, Junjie; Zhou, Xinglu; Yan, Youyou; Zhang, Bo; Lin, Nengming (Frontiers in Pharmacology, 2023)
Gastric cancer is the third leading cause of cancer related death worldwide. Due to the complexity and heterogeneity of gastric cancer, the development of targeted drugs is somehow limited, but is urgently needed. Since the expression of Bruton tyrosine kinase (BTK) was significantly associated with the prognosis of gastric cancer patients, we aimed to determine the anti-cancer activity of HZ-A-018, which was a novel derivative of ACP-196, in gastric cancer cells. As a result, HZ-A-018 presented a stronger anti-proliferation activity than ACP-196 via the substantial suppression of AKT/S6 pathway. In addition, HZ-A-018, but not ACP-196, exerted the synergistic effects in combined treatment with 5-FU both in vitro and in vivo, without exacerbating the adverse effects of 5-FU. Mechanismly, the combination of HZ-A-018 and 5-FU remarkably reduced the expression of RRM2, which played an essential role in proliferation and drug sensitivity in gastric cancer cells. In summary, our work demonstrated the stronger anti-cancer activity of HZ-A-018 than ACP-196 in gastric cancer cells, and revealed synergistic effects of HZ-A-018 and 5-FU combination probably through the inhibition of RRM2 via AKT/S6 pathway, thereby providing a promising therapeutic strategy in gastric cancer.